Conversational German revised and updated - Martin , Genevieve A; Bertram , Theodor; Kleinmann , Walter (New York Crown, 1993)
A language course in German and English developed for rapid learning and stressing conversationally useful words and phrases
Keywords: German language Conversation and phrase books English; German language German; Dictionaries